Evaluation of the Indoor Air Quality in Restaurants Before and After a Smoking Ban in Portugal - Madureira, Joana (2012)
On 14th August 2007, Portugal instituted a smoking ban in most indoor public places. The goal of this work was to quantify the effects of this ban on indoor air quality (IAQ) in Portuguese restaurants. Ten restaurants were investigated before and after the ban and the following indoor parameters measured: respirable suspended particulate matter (RSP), total volatile organic compounds (TVOC), benzene (C6H6), carbon monoxide (CO), carbon dioxide (CO2), temperature and relative humidity. Results show a statistically significant decrease in RSP and CO concentrations after the ban, as well as for TVOC and benzene concentrations. Additionally, the monitored CO2 concentrations widely exceeded 1800 mg·m-3 (reference for acceptable ventilation rates), suggesting inefficient ventilation of the indoor spaces. This paper provides the first comparison of IAQ in Portugal before and after the introduction of smoke-free law and these results confirm the positive impact of the law in the indoor air that became smoke-free after the legislation. This information should be provided to decision makers as it has significant health implications. This law thus appear to achieve the aim of protecting people from exposure to unwanted pollutants resulting from poor IAQ.